STATISTICAL STUDY OF THE NATURAL MOVEMENT OF THE POPULATION OF UZBEKISTAN (Web of Discoveries: Journal of Analysis and Inventions, 2025)
This article analyzes the population of the Republic of Uzbekistan, its formation and development, and its current state. The problems that have arisen in the population due to pandemic restrictions and the measures taken to eliminate them and mitigate the situation are analyzed. International experience is studied, problems in ensuring employment of the population are indicated, and directions for their elimination are proposed.